Moving beyond first-line treatment options for OCD - Chris Paxos, PharmD, BCGP, BCPS, BCPP (American Association of Psychiatric Pharmacists, 2022)
OCD is characterized by obsessions and compulsions that cause distress, are time-consuming, and interfere with a patient's social, occupational, or other areas of functioning. SSRIs are first-line pharmacologic treatment options and produce response rates of up to 60% in patients with OCD. Several potential strategies have been evaluated for enhancing patient response, including high-dose SSRI therapy, antipsychotic augmentation, and memantine augmentation. Three patient cases are used to explore treatment guidelines, evaluate existing literature, and provide pharmacotherapy recommendations for the management of patients with OCD when first-line therapy fails.